2017
DOI: 10.1111/joop.12181
|View full text |Cite
|
Sign up to set email alerts
|

A model of leadership motivations, error management culture, leadership capacity, and career success

Abstract: We integrated ideas from literature on error management culture, leadership motivation, and career development to create several contributions for the research literature. First, we examined two situational factorserror management/aversion culture perceptionsthat affect employees' leadership-relevant motivations. Second, we distinguish between two types of leader motivations, motivation to lead (MTL) and motivation to develop leadership skills (MTDL). We offer evidence of discriminant and predictive validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 67 publications
(102 reference statements)
5
38
0
10
Order By: Relevance
“…The results of our analysis suggest that the Brazilian version of the EMCS has a one-factor structure, but can also be represented in terms of four facets. The structure we uncovered is in line with the findings of the original study of the EMCS by van Dyck et al (2005) and with other studies using the scale (Cigularov et al, 2010;Fruhen & Keith, 2014;Jung & Yoon, 2017;Maurer et al, 2017). The Cronbach's alpha indicated that the Brazilian version has good internal consistency.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of our analysis suggest that the Brazilian version of the EMCS has a one-factor structure, but can also be represented in terms of four facets. The structure we uncovered is in line with the findings of the original study of the EMCS by van Dyck et al (2005) and with other studies using the scale (Cigularov et al, 2010;Fruhen & Keith, 2014;Jung & Yoon, 2017;Maurer et al, 2017). The Cronbach's alpha indicated that the Brazilian version has good internal consistency.…”
Section: Discussionsupporting
confidence: 87%
“…Frese and Keith (2015), and van Dyck et al (2005) argued that organizations in which specific error management practices are pervasive are more likely to display competitive advantages, such as learning, resilience, and innovation. In addition, the development of an error management culture can help to increase the motivation and the capacity of the leadership, as well as contributing to the professional development and career success of employees (Maurer et al, 2017;Mourão, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os valores pessoais revelam a disposição do indivíduo em atender a interesses coletivos e/ou individuais (Parks-Leduc, Feldman, & Bardi, 2015;Porto & Tamayo, 2008), bem como podem ser uma perspectiva de entendimento das inclinações individuais para terem um vínculo mais próximo com a carreira (Maurer, Hartnell, & Lippstreu, 2017) e com a organização (Blustein, 2013).…”
Section: Introductionunclassified